AB0424 Has the role of ana in differential diagnosis of connective tissue diseases been changed after technological developments?. (23rd January 2014) - Karadag, O.; Kilic, L.; Erbil, A. A.; Aydın, N. N.; Tuncer, O.; Akdogan, A.; Bilgen, S. A.; Sener, B.; Ertenli, I.; Kiraz, S.
Abstract : Background: The mostly recommended method used in the detection of auto-antibodies for ANA is immune fluorescent antibody technique (IFA). In parallel with technological developments, new patterns as actin, ku, granular chromosomes (DFS-70) are also reported. However, clinical significance of these findings is currently not very well understood. Objectives: We aimed to investigate the concordance of ANA results with clinical diagnosis of connective tissue diseases, and meanings of new patterns for autoimmune diseases. Methods: The results of Immunology laboratory between January - June 2012 was used for this study. Totally 2195 ANA-IFA results of 2114 patients who were followed in our rheumatology clinic were reevaluated. ANA analysis, the IFA method using Hep-2, and liver cells (Euroimmun, Germany) was performed and the results were reported by an experienced specialist in microbiology. Clinical data were obtained from hospital records. For each connective tissue disease and the IFA pattern, ANA titers were identified. The clinical significance of the IFA patterns in connective tissue diseases and other diseases were investigated. Results: Among the study group 850 (40.2%) patients had a connective tissue disease. 227 patients had non-inflammatory musculoskeletal disorders. Distribution and patterns of ANA positivity in patients were shown in table 1 . In 29 (11.4%) SLE patients, ANA was negative at the time of study. Seventeen of them had ANA positivity in previous tests. The other 9 ANA negative SLE patients were under treatment when tested and 3 (1.2%) patients were ANA (-) since the beginning of the disease. The frequency of newly reported patterns (cytoplasmic, ku, nuclear membrane, actin and dense fine granular (DFS70)) were as 11.8%, 0.6%, 1.8%, 0.4% and 9.7%, respectively. Regarding DFS70 pattern positive 104 patients; 52.8% did not have a rheumatic disease, but in 19.2% had RA (p <0.001). In nuclear membrane positive 17 patients, 8 didn't have a rheumatic disease, but 5 had RA. There was no difference between the groups regarding cytoplasmic, ku and actin patterns. Conclusions: ANA tests requested in rheumatology clinic can be false positive up to %35. However, only 12.3% of them had a titer ≥1/320. The sensitivity of the ANA in patients with SLE as assessed by IFA was more than 98%. Nuclear membrane and DFS70 patterns are not specific to any connective tissue disease and they can be detected positive in rheumatoid arthritis and in the absence of any rheumatic disease Disclosure of Interest: None Declared